Association between comorbidities and absence of chest pain in acute coronary syndrome with in-hospital outcome. (August 2016) - Manfrini, Olivia; Ricci, Beatrice; Cenko, Edina; Dorobantu, Maria; Kalpak, Oliver; Kedev, Sasko; Kneževic, Božidarka; Koller, Akos; Milicic, Davor; Vasiljevic, Zorana; Badimon, Lina; Bugiardini, Raffaele; et al.
Abstract: Background: To evaluate the impact of comorbidities on the management and outcomes of acute coronary syndrome (ACS) patients without chest pain/discomfort (i.e. ACS without typical presentation). Methods: Of the 11, 458 ACS patients, enrolled by the International Survey of Acute Coronary Syndrome in Transitional Countries (ISACS-TC;ClinicalTrials.gov :NCT01218776 ), 8.7% did not have typical presentation at the initial evaluation, and 40.2% had comorbidities. The odds of atypical presentation increased proportionally with the number of comorbidities (odds ratio [OR]: 1, no-comorbid; OR: 1.64, 1 comorbidity; OR: 2.52, 2 comorbidities; OR: 4.57, ≥ 3 comorbidities). Results: Stratifying the study population by the presence/absence of comorbidities and typical presentation, we found a decreasing trend for use of medications and percutaneous intervention (OR: 1, typical presentation and no-comorbidities; OR: 0.70, typical presentation and comorbidities; OR: 0.23, atypical presentation and no-comorbidities; OR: 0.18, atypical presentation and comorbidities). On the opposite, compared with patients with typical presentation and no-comorbidities (OR: 1, referent), there was an increasing trend (p < 0.001) in the risk of death (OR: 2.00, OR: 2.52 and OR: 4.83) in the above subgroups. However, after adjusting for comorbidities, medications and invasive procedures, atypical presentation was not a predictor of in-hospital death. Independent predictors of poor outcome were history of stroke (OR: 2.04), chronic kidney disease (OR: 1.57), diabetes mellitus (OR: 1.49) and underuse of invasive procedures. Conclusions: In the ISACS-TC, atypical ACS presentation was often associated with comorbidities. Atypical presentation and comorbidities influenced underuse of in-hospital treatments. The latter and comorbidities are related with poor in-hospital outcome, but not atypical presentation, per se.